RETRACTED: Analysis of the Associated Factors of Boarding Time in Yellow Zone Patients in Emergency Department - Ahsan Ahsan; Fitrio Deviantony; Setyoadi Setyoadi (Universitas Airlangga, 2017)
Introduction: Patient’s visits to the emergency room increase in number every year. The increasing number of hospital visits is directly associated with the increasing number of patients who wait in the emergency department. The yellow zone is a part of the emergency room that has become a place for the most increased patients to enter. This situation causes boarding time patient longer than usual. The aim of this research was to analyse the various factors that have been associated with boarding time in the yellow zone emergency department.Methods: This research was an analytic observational study with a cross-sectional approach. The number of samples was 78 respondents who were recruited with a non-probability sampling technique. The univariate and bivariate analysis was utilized to test the relationship between the variables. A further statistical test was conducted with linear regression to understand the most dominant factor.Results: The results showed a significant relationship between transfer time, laboratory turnaround time, diagnostic time, time arrival, insurance coverage, ratio nurse and patient and boarding time. Furthermore, multivariate analysis with linear regression showed a significant association between transfer time, laboratory turns around, and the ratio of nurses to patients with the boarding time.Conclusion: The findings from this study show that patient boarding time in the yellow zone should consider several factors. This research provides the output of the initial data as one of the basic considerations for service management and team minimum service standards in hospitals.